2020
DOI: 10.1002/prot.25983
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution structure of a partially folded insulin aggregation intermediate

Abstract: Insulin has long been served as a model for protein aggregation, both due to the importance of aggregation in the manufacture of insulin and because the structural biology of insulin has been extensively characterized. Despite intensive study, details about the initial triggers for aggregation have remained elusive at the molecular level. We show here that at acidic pH, the aggregation of insulin is likely initiated by a partially folded monomeric intermediate. High-resolution structures of the partially folde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…56 Previous studies have also indicated that the amyloid fibril formation for globular proteins, such as HI, occurs via partially unfolded intermediates that gradually associate to form the oligomers, eventually into well-ordered mature fibrils. 9,14,23,27,33,47,57,58 A partial unfolding of the monomeric globular protein produces a molten globule like structure that is comparable to the amyloidogenic protein intermediates, acting as the nucleating form. 29,50,55,[59][60][61] In the absence of zinc at physiological pH, HI is primarily present as a conformationally stable dimer;…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…56 Previous studies have also indicated that the amyloid fibril formation for globular proteins, such as HI, occurs via partially unfolded intermediates that gradually associate to form the oligomers, eventually into well-ordered mature fibrils. 9,14,23,27,33,47,57,58 A partial unfolding of the monomeric globular protein produces a molten globule like structure that is comparable to the amyloidogenic protein intermediates, acting as the nucleating form. 29,50,55,[59][60][61] In the absence of zinc at physiological pH, HI is primarily present as a conformationally stable dimer;…”
Section: Discussionmentioning
confidence: 99%
“…Coarsely identical to the initial monomeric structure of the protein in buffer solution, these monomeric structures produce the lesser known nucleus en route to HI fibrillation. 9,14,23,27,33,34,47,57 The nucleation step has been identified with the C-terminal end of the B chain helix turning away from the C-terminal end of the A chain helix. This causes a partial loss of helicity on the C-terminal of the A-chain, accompanied by a compromise of the intra-chain hydrophobic contacts between Leu 16A on A chain C-terminal helix and Leu 15B and Val 18B on the B chain helix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ratha et al, characterized, at high-resolution, the structure of a partially folded intermediate of insulin, suggesting that this state may represent the starting point of the aggregation process. The authors observed slight structural changes in this intermediate compared to the monomer, claiming that these changes lead to the formation of a hydrophobic cavity in the center of the protein that acts as a nucleation center for oligomer formation [ 78 ].…”
Section: Structural Commonalitiesmentioning
confidence: 99%